Preparation of high-dispersion Ni/C catalyst using modified lignite as carbon precursor for catalytic reforming of biomass volatiles. (15th August 2017) - Ren, Jie; Cao, Jing-Pei; Zhao, Xiao-Yan; Wei, Fu; Liu, Tian-Long; Fan, Xing; Zhao, Yun-Peng; Wei, Xian-Yong
Graphical abstract: Highlights: Demineralization caused the pore corrosion and decreased the activity of Ni/C. High Ni loading and well dispersed Ni/C was prepared by acid treatment of lignite. H2 O2 oxidation can improve the carboxyl group content of raw and modified lignite. Carboxyl group content is a key parameter for Ni/C preparation. Inherent minerals have a good influence on Ni/C for biomass volatile reforming. Abstract: Lignite is rich in oxygen-containing species (OCSs) and able to load Ni via ion exchange to prepare Ni/C catalyst. However, the OCSs usually exists in the form of organic salts, which can reduce the capacity of Ni ion exchange. In this paper, Shengli lignite (SL) was treated with HCl and HCl/HF to selectively remove the organic salts and insoluble minerals, respectively, and the modified lignite was oxidized by H2 O2 to further increase the carboxyl content. The treated lignite was used to prepare Ni/C catalyst and the activity for biomass volatile reforming was evaluated. The results show that demineralization (DM) caused the corrosion of pore structure of SL and gave a Ni/C catalyst with a low specific surface area (SSA) of 222.1 m 2 /g. Oxidation with H2 O2 further destroyed the structure of DMSL and provided a Ni/C with the lowest SSA of 141.1 m 2 /g. Acid wash (AW) with HCl resulted in the increase of ion exchange capacity of SL and gave a Ni/C catalyst with larger SSA, higher loading, lower particle size and well dispersion of Ni particle in comparison with SL and DMSL. H2 O2 treatment of AWSL significantly increased the amount of carboxyl group to 3.8 mmol/g and gave a Ni/C with the largest SSA of 291.1 m 2 /g, highest Ni loading of 17.3% and smallest Ni crystallite size of 3.4 nm, as well as most active for corncob volatile reforming.